Implementasi Geofencing dalam Monitoring Rute Pengiriman Kendaraan di Sebuah Perusahaan Ekspedisi - Joko Priono; Eko Budi Setiawan (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2017)
This paper describe a geofencing approach in monitoring the routes used in the delivery of vehicles in a expedition company. Continuous technological development of information systems provide a variety approach on how to monitor a vehicle on the road. One of those approach is geofencing. Geofencing itself is an innovative technology that enables remote monitoring of a specific geographic areas. It can make a virtual area called geofence on a virtual map with different size and shape. This virtual area would be able to tracked mobile objects that enter or leave these area, and even how long the objects inside the area. The mobile objects that are going to be tracked are object that have GPS Tracking Unit. GPS Tracking Unit is an application or a tool that is used to figure out the position of an object. The position are based on geographical coordinate, latitude and longitude, and the data is received through a Global Positioning System. The implementation of the geofencing are going to use library from Google API. The combination of GPS Tracking and geofencing would be able to track, prevent or even restrict on specific routes that are going to be used in vehicle delivery. Index Terms— Pengawasan, GPS Tracker, Geofence area, Route information, Google API